1986
DOI: 10.1038/clpt.1986.45
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of glucocorticoid suspensions after intra-articular administration

Abstract: Triamcinolone acetonide, triamcinolone hexacetonide, and a combination of betamethasone phosphate and acetate were given intra-articularly in different doses. Plasma levels of the steroids were measured and pharmacokinetic parameters were calculated. As a pharmacodynamic parameter for systemic steroid activity, plasma hydrocortisone levels were monitored for 3 weeks. Results indicate complete absorption from the site of injection over a period of 2 to 3 weeks. Because of its lower solubility, triamcinolone hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
124
1
4

Year Published

1987
1987
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(141 citation statements)
references
References 0 publications
4
124
1
4
Order By: Relevance
“…The metabolic pathway of intrasynovial corticosteroids has not been fully elucidated. The rate of absorption and duration of action are related to solubility of the compound, and triamcinolone hexacetonide is the most insoluble preparation currently available (16). Depending on the formulation, a steroid can be detected in synovial fluid up to 14 days after injection (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic pathway of intrasynovial corticosteroids has not been fully elucidated. The rate of absorption and duration of action are related to solubility of the compound, and triamcinolone hexacetonide is the most insoluble preparation currently available (16). Depending on the formulation, a steroid can be detected in synovial fluid up to 14 days after injection (29).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the steroid treatment group were administered a fluoroscopically guided IA injection of anesthetic (10 mg bipuvicaine) and corticosteroid (40 mg triamcinolone hexacetonide [2 ml at 20 mg/ml]). Triamcinolone hexacetonide was chosen as the active IA treatment because its formulation is the most insoluble of the corticosteroids (16) and has been found to have the most prolonged duration of effect (17). A steroid dose of 40 mg in conjunction with a local anesthetic was the regimen chosen, in accordance with the ACR recommendations for IA use in large weight-bearing joints (9).…”
Section: Methodsmentioning
confidence: 99%
“…Although there is no absolute proof that this decrease in enzyme activity was the result of steroid therapy, it is possible that the pharmacologic effects of these agents may last longer than do their direct effects in the joint. This could vary from a few hours to a few weeks, depending on their chemical composition (19,20). It might explain why the clinical improvement in patients treated with intraarticular steroids may last for many months (20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on patients have shown that, due to its lower solubility, T H is absorbed more slowly than triamcinolone acetonide, and that levels in the synovial fluid are maintained for over 2 weeks (26). Because of its prolonged action and the positive results demonstrated in other models of OA, it was of the utmost importance to determine the effects of TH in the dog model, which closely mimics human OA.…”
Section: Discussionmentioning
confidence: 99%